The Effect of Massage for The Common Cold Using Syzygium Aromaticum on Reducing Cough Symptoms in Toddlers at The Dede Child Health Center in Purwakarta in 2026 - Dede Yiyin Zdulhijjah; Armiyanti Armiyanti; Ewith Widiya Mareta (Journal of World Science, 2026)
Cough and cold symptoms in toddlers, as part of Acute Respiratory Infections (ARI), remain a common health problem with a high incidence rate. Common Cold Massage using Syzygium aromaticum is believed to provide relaxation and anti-inflammatory effects that may help relieve respiratory symptoms. This study aims to evaluate changes in cough and cold symptoms among toddlers following Common Cold Massage using Syzygium aromaticum at TPMB Dede Purwakarta, West Java, Indonesia, in 2026. This quasi-experimental study employed a one-group pretest-posttest design and was conducted at an independent midwifery practice (TPMB Dede Purwakarta) from February to May 2026. A total of 50 toddlers who met the inclusion criteria were recruited using total sampling. Data were collected using a cough and cold symptom observation sheet, a massage standard operating procedure checklist, and a questionnaire. Changes in symptom scores before and after the intervention were analyzed using the Wilcoxon signed-rank test. Cough and cold symptom scores significantly decreased following Common Cold Massage using Syzygium aromaticum (p = 0.001). Moderate symptoms decreased from 82% before the intervention to 10% after the intervention, while 16% of toddlers experienced no symptoms after treatment. These findings indicate an association between the intervention and reduced symptom severity. Common Cold Massage using Syzygium aromaticum was associated with a significant reduction in cough and cold symptoms among toddlers at TPMB Dede Purwakarta in 2026. However, the absence of a control group and the use of a single study setting may limit causal inference and the generalizability of the findings.